Evaluation of CA 15-3, Her-2/neu and estrogen/progesterone status in breast cancer patients treated by surgical removal and chemotherapy - Taha H Taha Al-siagh; Shahbaa A Al-bayati; Faris A Ahmed (University of Mosul, 2012)
Objective: This study was conducted to evaluate serum CA 15-3 in breast cancer patients after surgery and chemotherapy. The relationship between serum CA 15-3 and Her-2/neu, estrogen, or progesterone receptors were also studied in the breast cancer patients. Patients and methods: This study was conducted at Al-Jammhori Teaching Hospital, and Al-Zahrawi Private Hospital, Mosul, Iraq, during the period from January to Jun 2011. Fifty breast cancer women diagnosed by using triple assessments by a surgeon (history examination, ultrasound mammography, and fine needle aspiration cytology) were included in the study. Blood samples (5 mL) were taken from the patients and analyzed for serum CA 15-3 by monoclonal antibody technique. The blood samples were taken from the patients a week before and after one week of the operation and other blood samples were taken after two weeks of the first cycle of chemotherapy treatment. Combination therapy of 5-fluorouracil, epirubicin, cyclophosphamide, for three cycles every 21 days, was given to the patients, followed by three cycles docytaxil every 21 days. Samples from the tumor on paraffin sections taken from the patients were analyzed for Her-2/neu, estrogen and progesterone receptors by immunochemical methods. Results: Serum CA 15-3 was significantly decreased by 54% (p ≤ 0.001) after surgical removal of the cancer compared with results before surgery. Chemotherapy of the patients further decreased serum CA 15-3 significantly by 78% (p ≤ 0.001) compared with the results before surgery. CA 15-3 and tumor size in positive Her-2/neu patients were significantly higher than in negative Her-2/neu patients. However, serum CA 15-3 and tumor size in positive estrogen patients were significantly lower than in negative estrogen patients. In progesterone positive patient's serum CA 15-3 was only significantly (p ≤ 0.001) lower than in the negative progesterone patients. Mean ages was significantly (p ≤ 0.001) higher in positive Her-2/neu patients than in negative Her-2/neu patients. However, mean ages was significantly (p ≤ 0.001) higher in positive estrogen and progesterone patients than in negative receptors. Metastasis occurred in 39 patients (78 %) out of the studied patients. Negative significant correlation was noticed between Her 2/neu and estrogen receptors (r= - 0.745, p ≤ 0.001). Negative significant correlation was also noticed between Her 2/neu and progesterone receptors (r= - 0.786, p ≤ 0.001). Weak but significant correlation was found between serum CA 15-3 and tumor size (r= 0.281, p≤ 0.05). Conclusion: CA 15-3 and Her 2/neu are useful tumor markers for diagnosis of breast cancer in the treatment through surgery and chemotherapy. The co-expression between hormonal and Her-2/neu receptors is negative. The need for more sensitive tumor markers is still wanted.